2018
DOI: 10.1080/13607863.2018.1460743
|View full text |Cite
|
Sign up to set email alerts
|

Spirituality and wellbeing in later life: a multidimensional approach

Abstract: These findings demonstrate that not all spirituality domains are equally dominant in people's lives or positively associate with SWB. They also suggest that encouraging elderly people to develop their personal spirituality and self-growth may contribute to their wellbeing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 48 publications
2
29
0
2
Order By: Relevance
“…First and foremost, the findings indicated that online religious Q&A for elders are characterized by a variety of contents, question types and styles. The observed distinction between Q&A of interest to people of 'all ages' and those relevant only to 'later life' supports the portrayal of religious activity as multidimensional (Lifshitz et al, 2019) and corroborates the claim that older people's involvement in religious each aspect is likely to vary and may change with age (Wang et al, 2014).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…First and foremost, the findings indicated that online religious Q&A for elders are characterized by a variety of contents, question types and styles. The observed distinction between Q&A of interest to people of 'all ages' and those relevant only to 'later life' supports the portrayal of religious activity as multidimensional (Lifshitz et al, 2019) and corroborates the claim that older people's involvement in religious each aspect is likely to vary and may change with age (Wang et al, 2014).…”
Section: Discussionsupporting
confidence: 77%
“…In line with the approach that does not separate spirituality from religiosity, spiritual wellbeing was defined as a satisfactory relationship with a transcendent deity and contact with one's inner being, as well as interaction and association with the religious community and environment (Fisher, 2011). Many studies have shown the importance of religion for spiritual wellbeing, especially in later life (e.g., Lifshitz et al, 2019;Malone & Dadswell, 2018;Shaw et al, 2016). Towards the end of their lives, people undertake religious involvement in the pursuit of physical healing, comfort and strength (Wang et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…It has three dimensions: a connection to oneself, a connection to others and nature, and a connection to transcendence ( Meezenbroek et al, 2012 ). Studies have revealed that spirituality can improve SWB ( Kamitsis and Francis, 2013 ), particularly in elderly people ( Lifshitz et al, 2019 ) and teenagers ( Sarriera et al, 2014 ). Another research explored spiritual prepositional variables and showed how mindfulness can improve individual spiritual growth ( Matiz et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Elderly needs are not only related to meeting their physical and financial needs that are currently the focus, but it also refers to their overall needs in life. At present, the increase in the number of elderly residents is not accompanied by an increase in the well-being of the elderly (Lifshitz, Nimrod and Bachner, 2019).…”
Section: Introductionmentioning
confidence: 82%